DEVELOPMENT OF BUSY BOOK LEARNING MEDIA BASED ON THE SYLLABLE METHOD TO IMPROVE READING ABILITY OF CHILDREN AGED 5-6 YEARS - Mira Silfia; Asih Menanti; Aman Simare-mare (Sensei International Journal of Education and Linguistic, 2021)
The reading development of children aged 5-6 years on average has not yet developed, marked by children still needing teacher guidance in pronouncing letters and not distinguishing between vowels and consonants. For this reason, it is necessary to develop media that can attract attention and help children learn to read. The objectives of this study are: 1) Knowing the level of feasibility of the use of busy book learning media based on the syllable method to improve the reading ability of children aged 5-6 years. 2) Knowing the effectiveness of developing busy book learning media based on the syllable method to improve the reading ability of children aged 5-6 years. The method used in this research is developing a 4-D model (four D model) consisting of 4 main stages, namely: Define, Design, Develop, and Disseminate. The subjects of this study were students of group B RA Al-Hidayah Air Pinang Village in the even semester of the 2020/2021 academic year, totalling 11 people consisting of 4 girls and 7 boys. The object of this research is the development of busy book learning media based on the syllable method to improve the reading ability of children aged 5-6 years at RA Al-Hidayah, Air Pinang Village. The data collection techniques in this study were 1) expert team validation questionnaire sheets, 2) student and teacher response questionnaire sheets, 3) reading ability test observation sheets for children aged 5-6 years. The results of this study indicate that the busy book media based on the syllable method is very feasible to use, and the effectiveness of reading learning increases after using the busy book media based on the syllable method, which has implications for the average score of the child's initial test, which is 34.54 and on the final test it increases to 77. .72 with an increase in value of 43.18. 2) questionnaire responses from students and teachers, 3) observation sheets for reading proficiency tests for children aged 5-6 years. The results of this study indicate that the busy book media based on the syllable method is very feasible to use, and the effectiveness of reading learning increases after using the busy book media based on the syllable method, which has implications for the average score of the child's initial test, which is 34.54 and on the final test it increases to 77. .72 with an increase in value of 43.18. 2) questionnaire responses from students and teachers, 3) observation sheets for reading proficiency tests for children aged 5-6 years. The results of this study indicate that the busy book media based on the syllable method is very feasible to use, and the effectiveness of reading learning increases after using the busy book media based on the syllable method, which has implications for the average score of the child's initial test, which is 34.54 and on the final test it increases to 77.72 with an increase in value of 43.18.